Trabalhadores na "fronteira": experiências dos sacoleiros e laranjas em Foz do Iguaçu - Ciudad Del Este (1990/2006) - Davi, Elen Patricia de Jesus Silva (2008)
This dissertation aims to argue part of the experiences and the way of living of the people who contraband goods from Paraguay to Brazil, called sacoleiros and laranjas, as well as their work relation and their relation with Foz do Iguaçu, a town which was built from the established trade in the border of Brazil and Paraguay. Having this focus, I intended to understand and discuss these workers relations with the public and private organs (such as the IRS, the City hall, the Press), starting from their dynamics, their forged work strategies, as well as the established meanings in relation to this activity and the city. I also intended to understand how these people interact as a working class, from their paths, migrations, individual and collective experiences, as well as their own ways of living, inserting themselves, acting and interpreting the urban space. Finally, unmasking the dynamics of these workers also turned out to be a way of placing those workers' memoirs as a part of the construction of the social spaces, reaffirming their condition as production agents in the city of Foz do Iguaçu